2016
DOI: 10.1177/1687814016651207
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of wave-driven pore-water pressure and wave attenuation in a sandy seabed

Abstract: Wave-seabed interaction has become a big concern of coastal researchers and engineers in the past decades as it may largely contribute to the seabed instability and failure of marine foundations. A series of laboratory experiments are carried out in a wave flume to study the wave-driven pore-water pressure in a sandy seabed and the attenuation of wave height. Waves propagating over a sandy seabed lead to oscillatory excess pore-water pressures within the porous seabed. Amplitude of pore-water pressure within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It can be clearly seen that the measured excess pore-pressure amplitudes decrease abruptly as the backfilled depth increases from 0 to D. The primary reason for this could be that the wave-induced excess pore-water pressure around the pipeline decreases with increasing backfilled depth at certain backfilled depths. This is consistent with previous studies [39]. The amplitude of the excess pore pressure in the vicinity of the pipeline increases significantly as the backfilled depth increases from D to 9D/4.…”
Section: Effects Of Backfilled Depthsupporting
confidence: 93%
“…It can be clearly seen that the measured excess pore-pressure amplitudes decrease abruptly as the backfilled depth increases from 0 to D. The primary reason for this could be that the wave-induced excess pore-water pressure around the pipeline decreases with increasing backfilled depth at certain backfilled depths. This is consistent with previous studies [39]. The amplitude of the excess pore pressure in the vicinity of the pipeline increases significantly as the backfilled depth increases from D to 9D/4.…”
Section: Effects Of Backfilled Depthsupporting
confidence: 93%
“…With the same framework, Hsu and Jeng (1994) later derived the analytical solution to Biot's equations for the case of finite soil thickness, which can converge to the above solution by Yamamoto et al (1978) and Madsen (1978) if the soil thickness approaches infinity. The validity of these analytical solutions have been confirmed by both one-dimensional tests using cylindrical-shaped apparatuses (Chowdhury et al, 2006;Liu et al, 2015) and flume experiments (Tsui and Helfrich, 1983;Chang et al, 2007;Zhang et al, 2016;Zhai et al, 2018). A detailed review of the previous investigations on the wave-seabed interaction can be found in Jeng (2003;2013;2018).…”
Section: Introductionmentioning
confidence: 60%
“…Since the 1950s, numerous experimental studies have been performed to characterize the damping of waves on porous structures. Savage was one of first research scientists to study the wave interaction with a permeable seabed, modeling the engineered solution based on porous bed in an open channel 21‐26 . One of first works on the engineered solution using gabion weir has been given by Stephenson 27‐30 .…”
Section: Introductionmentioning
confidence: 99%